RELIGIOUS PLURALISM IN MUSLIM-MAJORITY COUNTRIES: Comparing Gorontalo, Indonesia and Negeri Sembilan, Malaysia - Hunowu, Momy; Kamaruzzaman, Kartini; Pakuna, Hatim Badu; Fata, Ahmad Khoirul (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
Indonesia and Malaysia, as Muslim-majority nations, are recognized for their tolerance of other religious groups. However, this study highlights underlying challenges threatening social stability in both countries. Focusing on Gorontalo, Indonesia, and Negeri Sembilan, Malaysia, the research examines the dynamics of religious pluralism and its societal challenges. Using a qualitative approach, main data were gathered through interviews with interfaith leaders, teachers, activists, and officials. The findings reveal that, while harmony and interfaith dialogue exist, challenges persist. In Gorontalo, minority communities face difficulties in constructing places of worship and acquiring suitable religious teachers. In Negeri Sembilan tensions arise over proper use of “religious plurality” or “pluralism” and the use of the term “Allah” by the Christians. Apparently, on top of the existing efforts other creative ways need to be used to strengthen religious harmony catering for the ever evolving social complexities in both regions.